Determinants of the prolongation of the yips in golfers: The roles of social support and overcommitment to sport - Kojiro Matsuda; Yasuo Susaki; Eriko Aiba; Yoshio Sugiyama (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2022)
The yips are the loss of automated and finely controlled motor behavior in sport, affecting many golfers. Although studies have examined their causes and treatment, the social and psychological factors that contribute to their duration in golfers remain unknown. This study examined whether overcommitment and social support are related to prolonged symptoms of yips. The participants included 54 yips-affected golfers who completed measures to identify those who were overcommitted and explore their experiences with the yips and social support. Although there was a significant relationship between prolonged symptoms of the yips and overcommitment, social support was not related to its duration. The results contribute to the understanding of the prolongation of the yips in golfers and may apply to players in other sports.